Extern styrning och modularisering av styrning till Bioloid robot - Laving, Tobias; Lind, Sebastian (My University, 2017)
This thesis carried out on behalf of Cybercom and is about development of a unit which can process sound and images. Predetermined objects are going to be recognized and a user can give voice commands. The unit is made of two lesser units, a Raspberry pi 3 and a Bioloid Robot. The robot is built as a human body and can walk on an horizontal plane. These two units will be able to communicate through serial communication via a USB cable. To achieve sound and image processing the Raspberry Pi has been provided with a camera and a USB microphone. The functionalities have been divided in three different modules. One module is responsible for image processing with OpenCV and the use of the Viola-Jones method to recognize selected objects. Another one manage voice commands with help of CMU pocketsphinx. The third module deals with the serial communication. Development on the Raspberry Pi has been done in C++ while the Bioloid robot uses C code. To show the ability of the combined unit a demonstration was developed. The demo is using all of the projects resulting resources to affect the units actions. The project and demo have been developed in a way that hopefully encourage further development.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science